La Geopolítica como factor de análisis de los conflictos externos en el Perú. - TRELLES VIZQUERRA, JAVIER HERNAN (2022)
Since its inception, the human being has experienced the imposed weight of the earth's surface, so the peoples adapted to the hostile conditions of the environment to survive. With the passing of time, these societies perceived the importance of geographical influence in the life of the States, and from this, they began systematic studies of the subject. This discipline called "Geopolitics" has been used as a tool to evaluate the influence of the geographical scope of nations and its usefulness for the design of efficient policies for the control, protection and search for harmony of the states. Globalization has made possible the development of information and communication technologies, especially with the internet; networks and information systems that have taken an important role in society, therefore, their reliability and security are essential aspects for the proper development of military, economic, social and political activities. The value of the elements, factors and scenarios that concur in the domain of a given space is nowadays an independent science. The automation of such factors and elements is called Geopolitics. The classic conception of geopolitics within the area of ​​strategic studies is related to the capabilities that a state can or should have to achieve certain objectives. In other words, it would determine the defense qualities of a state, so that decision-making can be carried out under a better perception of security and development.              Generally, development initiatives are provided by the state entity, based on the ideal form and result of a national geostrategy supported by society, where they cover security aspects, so that in this way the states reach the strategic stature of power median in the region. Peru, despite being a country with a low population density index and with a great diversity of natural resources, presents human development problems, due to poor demarcation, occupation and administration of the territory, including the poor exploitation of available resources. In this sense, this study aims to systematize the set of processes and interactions that occur during decision-making by decision-makers in matters of strategic security.   At the same time, this referential framework will serve as support so that from it a decision-making model can be built and applied that integrates the elements of geopolitical analysis in the solution of external conflicts. Taking into account that the border problems for Peru with neighboring countries have been proven to be constant, either by sea or by land and which are marked in national history, the researcher maintains that the intellectual contribution based on the This study will be of great benefit to the development and strategic security of the scientific-methodological community made up of the Joint Command of the Armed Forces, the National Police of Peru and the Members of the National Diplomatic Corps.           The information systematized in the present study will allow predicting scenarios through an analysis of the basic elements of Geopolitics, which evaluates the different edges of a problem, in relation to the application of a model for decision making and that contributes to establishing a route strategic security for the country. In a complex scenario, the conclusions of this research will provide a contribution to the academic community, analysts and scholars at a national and international level.